Antimycobacterial and Antifungal Activities of Leaf Extracts From Trichilia emetica - Lydia Chenesai Mugayi; Stanley Mukanganyama (Scientifica)
The global problem of infectious and deadly diseases caused by microbes such as candida and mycobacteria presents major scientific and medical challenges. Antimicrobial drug resistance is a rapidly growing problem with potentially devastating consequences. Various pathogens can cause skin infections, such as bacteria, fungi, and parasites. Antimicrobial resistance has caused the urgency to seek alternative treatment options from available natural resources. Plant-derived medicinal compounds can provide novel alternative treatment avenues against pathogenic microbes. The objective of this study was to determine the antimycobacterial and antifungal activity of leaf extracts of Trichilia emetica against Mycobacteria smegmatis, Mycobacteria aurum, Candida tropicalis, and Candida albicans. The leaf extracts were prepared using hexane, ethyl acetate, acetone, dichloromethane (DCM), methanol, ethanol, water, DCM:methanol, and 70% ethanolic aqueous solution. The microbroth dilution was used to determine the minimum inhibitory concentration (MIC) of each extract against the four test organisms. The mode of action by which these extracts inhibit growth was also investigated. The effects of the extract on the cell wall of C. tropicalis were determined using the sorbitol assay. The effects of the extracts on the membrane integrity of the test organisms were determined using propidium iodide, which binds to nucleic acids, and the Bradford reagent, which reacts with proteins. The ethyl acetate and 70% ethanolic aqueous extracts were most potent against the organisms tested with MICs ranging from 125 to 1000 μg/mL. However, the two extracts did not inhibit the growth of C. tropicalis in the presence of sorbitol. The extracts caused the leakage of nucleic acids and proteins in C. tropicalis and M. smegmatis only and not in M. aurum. It is concluded that the leaf extracts of T. emetica have antimycobacterial or antifungal activities. The disruption of cell membranes resulting in protein and nucleic acid leakage could be the plant’s possible mode of action.